Pengaruh Bentuk Kemasan, Desain Produk Dan Bahan Kemasan Terhadap Minat Beli Konsumen : (Studi Kasus Kopi Yamira) - Suma, Ebitrianto; Yusuf, Susanto Ali; Umar, Julkifli (JURNAL ADMINISTRASI BISNIS (JAB), 2023)
This study aims to investigate and analyze the effect of packaging shape, product design, and packaging material on intention to buy. 100 purposive samples were taken during research by using multiple regression analysis as an analysis tool. The result shows that packaging shapes, product design, and packaging material have a significant impact on buying intention. The existing coffee YAMIRA packaging proves to have a significant relation to the product attribute above.